Oral Microbiota Is Associated With Immune Recovery in Human Immunodeficiency Virus-Infected Individuals - Xie, Yirui; Sun, Jia; Hu, Caiqin; Ruan, Bing; Zhu, Biao (Frontiers in Microbiology, 2021)
The role of the oral microbiota in HIV-infected individuals deserves attention as either HIV infection or antiretroviral therapy (ART) may have effect on the diversity and the composition of the oral microbiome. However, few studies have addressed the oral microbiota and its interplay with different immune responses to ART in HIV-infected individuals. Salivary microbiota and immune activation were studied in 30 HIV-infected immunological responders (IR) and 34 immunological non-responders (INR) (≥500 and <200 CD4+ T-cell counts/µl after 2 years of HIV-1 viral suppression respectively) with no comorbidities. Metagenome sequencing revealed that the IR and the INR group presented similar salivary bacterial richness and diversity. The INR group presented a significantly higher abundance of genus Selenomonas_4, while the IR group manifested higher abundances of Candidatus_Saccharimonas and norank_p_Saccharimonas. Candidatus_Saccharimonas and norank_p_Saccharimonas were positively correlated with the current CD4+ T-cells. Candidatus_Saccharimonas was positively correlated with the markers of adaptive immunity CD4+CD57+ T-cells, while negative correlation was found between norank _p_Saccharimonas and the CD8+CD38+ T-cells as well as the CD4/CD8+HLADR+CD38+ T-cells. The conclusions are that the overall salivary microbiota structure was similar in the immunological responders and immunological non-responders, while there were some taxonomic differences in the salivary bacterial composition. Selenomona_4, Candidatus_Saccharimonas and norank _p_Saccharimonas might act as important factors of the immune recovery in the immunodeficiency patients, and Candidatus_Saccharimonas could be considered in the future as screening biomarkers for the immune responses in the HIV-infected individuals.